Humidity and specimen preparation procedure: influence on compressive strength of concrete blocks - Parsekian,Guilherme Aris (2021)
abstract: It is extremely important that the quality control of the concrete block used in structural masonry is conducted based on standard procedures that allow reliable estimation of the properties of these components. This work aims to analyze and evaluate the influence of the concrete block moisture on the result of the compression test. Hollow concrete blocks were prepared and subsequently maintained in different environments for various periods of time and under different conditions of temperature and humidity to determine the influence of the type of drying on the relative humidity of the block at the time of testing and consequently on its compressive strength. As a conclusion, it can be stated that, because it is necessary to use water in the process, the grinding rectification of the faces of the blocks led them to have high humidity, above 70%. If tested in this condition, the results of the compressive strength tests will be lower than that of blocks under usual environmental conditions. No differences were found in the average block strength when they were kept dry in the controlled environment of the laboratory during periods of 24 or 48 h. After grinding, it is not necessary to dry the blocks inside an oven at 40ºC before the tests; simply leaving them at a usual room temperature of 23ºC and humidity of 40 ± 5% for 24h is sufficient. The attempt to accelerate drying in an oven at 100ºC is not adequate because this leads to an increase in the compressive strength. From the results, it was possible to determine expressions to correlate the compressive strength as a function of the moisture of the block at the time of the test. The best-fit expressions are distinct for each block type, but the formulations are consistent in indicating a considerable difference in resistance as a function of moisture.